Short Communication: Morphological, biochemical, and molecular identification of cellulolytic bacteria isolated from feces of endemic tropical herbivores - SRI SUHARTI; NUR NOVRARIANI; KOMANG G. WIRYAWAN (Society for Indonesian Biodiversity, 2023)
Abstract. Suharti S, Novrariani N, Wiryawan KG. 2023. Short Communication: Morphological, biochemical, and molecular identification of cellulolytic bacteria isolated from feces of endemic tropical herbivores. Biodiversitas 24: 4046-4051. Indonesia has endemic herbivores that consume lignocellulose feedstuffs including grass, tree foliage, rice straw, and legume, indicating the presence of cellulolytic bacteria in their gastrointestinal tracts. Therefore, the aim of this study was to isolate and identify cellulolytic bacteria from the feces of tropical endemic herbivores, including anoa (Bubalus depressicornis), banteng (Bos javanicus), muntjak (Muntiacus muntjak), and timor deer (Rusa timorensis). Bacteria were isolated using the serial dilution technique and screened on Carboxy Methyl Cellulose (CMC) media. The selected isolates were identified based on their morphological and biochemical characteristics, cellulase enzyme activity, and molecular identification of 16S rDNA. The result showed that a total of five bacterial isolates were isolated from feces of anoa, banteng, muntjak, and timor deer. In addition, isolates exhibited characteristics of facultative anaerobes with gram-positive coccus, fermenting glucose, fructose, sucrose, starch, and cellulose. Based on cellulolytic index, isolates from anoa and banteng feces showed high cellulolytic activity with an index of about 1.2, indicating their potential as cellulose-degrading bacteria. Molecular identification and phylogeny analysis of cellulolytic bacteria isolates from anoa and banteng feces showed 100% similarities with Enterococcus faecium. Therefore, bacteria from feces of tropical endemic herbivores, especially anoa and banteng, possess cellulolytic activity and have potential as cellulolytic probiotic for ruminants that feed on forage-based diet. This is the first study to document the cellulolytic activity of anoa, and banteng feces.